Exosomes Derived From CircAkap7-Modified Adipose-Derived Mesenchymal Stem Cells Protect Against Cerebral Ischemic Injury - Xu, Limin; Ji, Haifeng; Jiang, Yufeng; Cai, Liying; Lai, Xiaoyin; Wu, Feifei; Hu, Rongguo; Yang, Xuelian; Bao, Huan; Jiang, Mei (Frontiers in Cell and Developmental Biology, 2020)
Background: Cerebral ischemic injury is a complicated pathological process. Adipose-derived stromal cells (ADSCs) have been used as a therapeutic strategy, with their therapeutic effects chiefly attributed to paracrine action rather than trans-differentiation. Studies have shown that circAkap7 was found to be downregulated in a mouse model of transient middle cerebral artery occlusion (tMCAO). Methods: To explore whether exosomes derived from circAkap7-modified ADSCs (exo-circAkap7) have therapeutic effects on cerebral ischemic injury, a mouse model of tMCAO, as well as an in vitro model of oxygen and glucose deprivation-reoxygenation (OGD-R) in primary astrocytes, were used. Results: Results showed that treatment with exo-circAkap7 protected against tMCAO in mice, and in vitro experiments confirmed that co-culture with exo-circAkap7 attenuated OGD-R-induced cellular injury by absorbing miR-155-5p, promoting ATG12-mediated autophagy, and inhibiting NRF2-mediated oxidative stress. Conclusion: We demonstrate here that exo-circAkap7 protected against cerebral ischemic injury by promoting autophagy and ameliorating oxidative stress.